The Reality of Financial Technology and Artificial Intelligence for Supporting the Financial and Banking Sector -Case Study of AL SALAM Bank of M’sila - امباركي, ياسمين; بن كشيدة, سامية (جامعة المسيلة, 2022)
Abstract: In this study we sought to highlight on fintech and artificial intelligence, which formed A revolution in financial systems, where the study aimed to reveal the role of fintech and intelligence The Algerian banking sector has increased its efficiency, and an integrated relationship has been noted between them. We did an interview, depending on the information Rasat's previous father Seen, Rasa's father came up with the important role that both AI play. And financial technology in developing and upgrading the efficiency of the banking sector, as we have come up with a set of Suggestions and recommendations enable Algeria to implement its own strategy and move towards investment in
Keywords: -- keywords: fintech, financial services, artificial intelligence,.Technology